1986
DOI: 10.1161/01.cir.73.2.276
|View full text |Cite
|
Sign up to set email alerts
|

Left ventricular pulsus alternans in patients with hypertrophic cardiomyopathy and severe obstruction to left ventricular outflow.

Abstract: 276-285, 1986. FOR OVER 100 years pulsus alternans, characterized clinically by alternating strong and weak beats on palpation of peripheral pulses, has been considered a sign of myocardial disease.' Pulsus alternans most commonly occurs in the setting of increased afterload, such as aortic stenosis2' and hypertension,4'5 especially in the setting of myocardial failure. However, pulsus alternans has also been observed in patients with cardiomyopathies of a variety of etiologies, including hypertrophic cardi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

1988
1988
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 57 publications
0
9
0
Order By: Relevance
“…This contradicts the general view that the PES contractility alternans represents more or less abnormal hearts or unphysiological cardiac conditions [14][15][16].…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…This contradicts the general view that the PES contractility alternans represents more or less abnormal hearts or unphysiological cardiac conditions [14][15][16].…”
Section: Discussionmentioning
confidence: 74%
“…We have confirmed that this holds consistently under widely changed end-diastolic volume, heart rate above 80-100 beats/min, and temperature (33-38°C) as well as under intracoronary infusions of Ca 2ϩ , catecholamines, pentobarbital, and ryanodine, and under global postischemic stunning in the canine excised, cross-circulated heart [1-10].We therefore doubted the general view that PES contractility potentiation would decay exponentially or monotonically in normal hearts under physiological conditions [11][12][13] but would decay in alternans in abnormal hearts or under unphysiological conditions [14][15][16][17]. However, whether the PES contractility usually decays in alternans or exponentially in the canine in situ heart, which is more physiological than the excised, cross-circulated one, has not yet been documented.…”
mentioning
confidence: 99%
“…Multiple heart diseases are associated with an increased vulnerability to alternans, particularly heart failure ( Kodama et al, 2004 ; Wilson et al, 2009 ), as well as hypertrophic cardiomyopathy ( Cannon et al, 1986 ), or myocardial infarction ( Gardner et al, 2015 ). It is known that cardiac remodeling in heart failure and other diseases alters both intracellular calcium release ( Lindner et al, 2002 ) and reuptake ( Kho et al, 2012 ) within cardiomyocytes.…”
Section: Introductionmentioning
confidence: 99%
“…Severe left ventricular systolic dysfunction is the primary cause of pulsus alternans but other causes have been reported in humans including aortic stenosis [4, 5], hypertrophic obstructive cardiomyopathy [6], mitral stenosis [7], prosthetic valve dysfunction [8], and during dobutamine infusion [9, 10]. Right ventricular pulsus alternans has been reported in cases with severe right ventricular failure, primary pulmonary hypertension, prosthetic mitral valve thrombosis, diastolic or systolic left ventricular dysfunction, reactive airway disease, pulmonary embolus, and mitral stenosis [1113].…”
Section: Discussionmentioning
confidence: 99%